Trends in Positive Treponemal Test Results Among Service Recipients at Bamrasnaradura Infectious Diseases Institute: A Five-Year Retrospective Study - Thongyen, Supeda; Matsree, Kasama; Wongsasiripat, Phanasa (Journal of Bamrasnaradura Infectious Diseases Institute, 2026)
This retrospective analytical study aimed to examine five-year trends in positive Treponema test results among service recipients at Bamrasnaradura Infectious Diseases Institute. Data were obtained from laboratory records and patient databases between October 1, 2021, and September 30, 2025. Descriptive statistics, including frequency, percentage, annual percentage change, and simple linear regression analysis, were used to assess trends over time. A total of 7,278 individuals underwent Treponema testing, of whom 608 (8.35%) had positive results. The number of positive cases increased from 98 in 2021 to 190 in 2025, representing a cumulative increase of 93.9%. Although the number of positive cases declined by 27.6% in 2022, a continuous upward trend was observed from 2023 onward, with a 41.8% increase in 2025 compared with the previous year. Linear trend analysis yielded the equation Y = 72.2 + 24.7X (R² = 0.76), indicating a clear increasing trend in positive Treponema test results throughout the study period. The increasing trend of positive Treponema test results reflects a growing burden of syphilis and increased healthcare service demands, particularly in counseling, treatment coordination, and long-term patient follow-up. These findings provide important evidence for workforce planning and the development of nursing competencies in risk assessment, clinical decision-making, counseling, and patient follow-up. Strengthening these competencies may contribute to improved quality of care and support sustainable syphilis control efforts.